Transformations of scientific atheism in Ukraine during Perestroyka - Oleg Kyselov (Cхід, 2017)
The article deals with the changes in theory and methodology of the Soviet Ukraine scientific atheism of the second half of the 1980's. Three factors affecting transformations in scientific atheism are distinguished by the author: liberalization of state-church relations, desecularization, and public critique of atheism. Published books and articles as well as archives of atheistic institutions are examined on displaying three topics: approaches to religion, the place of religion in public space of the Soviet society and self-representation of scientific atheism. Tolerant attitude to religiosity, believers, and Church is found in Perestroyka's scientific atheism texts. Nevertheless, secularist and atheist guidelines were still present there - religion should pass away and atheism is a truthful worldview. Beside this it was found that scholars dissociated themselves from the classic Marxist thesis on religion and social history (e.g. class conflict approach), in that way overcoming atheistic dogmatism of the 1960-1970's. During Perestroyka the atheism has become one of the main research objects - the scholars of atheism had to ground its existence in the future society - society without religion. Whereas the scientific atheist didn't believe in the vanishing of religion in the nearest perspective. The author concludes that Perestroyka's scientific atheism was exposed to methodological transformations drawing it closer to the academic study of religion (Religionswissenschaft).